Weaving Life into Art: "Reclaiming the Earth to Reclaim It All," an interview with Julieth Morales, an indigenous artist from the Misak community - Guimarães, Silvia; Nieto Moreno, Juana Valentina (Anuário Antropológico, 2023)
The artworks of Julieth Morales, a Misak indigenous individual born in 1992, were on display at the La Tertulia Museum in April 2019 in the city of Cali, Colombia, when one of the interviewers (Sílvia Guimarães) visited the museum and encountered the greatness of the exhibition called "Srape Poto Tul-Yu" ("The Last Circle"). In each painting and image, Julieth Morales, her body, her territory, and her Misak people composed a critique of colonization and its repeated attempts to obscure Misak cosmology. The productions included videos, photographs, and serigraphs where her body burst into mythical narratives about territoriality and the dynamics of cosmological transformation. Various themes and technological media were explored in the construction of each artwork.